1994
DOI: 10.1084/jem.180.3.907
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 12, interferon gamma, and tumor necrosis factor alpha are the key cytokines of the generalized Shwartzman reaction.

Abstract: SummaryThe Shwartzman reaction is elicited by two injections of lipopolysaccharide (LPS) in mice. The priming LPS injection is given in the footpad, whereas the lethal LPS challenge is given intravenously 24 h later. The injection of interferon 3, (IFN-'y) or interleukin 12 (IL-12) instead of the LPS priming injection induced the lethal reaction in mice further challenged with LPS. Antibodies against IFN-q/when given together with the priming agent, prevented the lethal reaction in mice primed with either LPS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
147
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(159 citation statements)
references
References 42 publications
11
147
0
1
Order By: Relevance
“…17 Similar findings were reported in a model of a generalized Shwartzmann reaction in mice. 24 In baboons challenged with Escherichia coli 23 the systemic release of IL-12 p40 and p70 was also reported. Our study confirms that circulating levels of IL-12 are also increased in human sepsis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…17 Similar findings were reported in a model of a generalized Shwartzmann reaction in mice. 24 In baboons challenged with Escherichia coli 23 the systemic release of IL-12 p40 and p70 was also reported. Our study confirms that circulating levels of IL-12 are also increased in human sepsis.…”
Section: Discussionmentioning
confidence: 95%
“…7 The role of IFN-g during in vitro LPS-challenge, 30 in vivo endotoxemia in mice, [16][17][18][19][20] or the generalized Shwartzman reaction in mice, 24,33,34 has been well established. Disseminated intravascular coagulation and shock associated with meningococcal sepsis are considered to be the clinical counterparts of the ''classical'' generalized Shwartzmann reaction.…”
Section: Interferon Gmentioning
confidence: 99%
“…The 'priming agent' may be cortisone itself, through non-specific mechanisms involving monocytes and natural killer (NK) cells [15]. Tumor necrosis factor-a (TNF-a), interferon-g (IFN-g) and interleukin-2 (IL-2) have been identified as key cytokines for the generalized Shwartzman reaction [16]. Thus the maternal immune system is suppressed in one model, but primed to respond in the other.…”
Section: What Is the Immunology Of Pregnancy?mentioning
confidence: 99%
“…B9 cells were harvested from tissue culture flasks, seeded into microtitre plates (Nunc, Roskilde, Denmark) at the concentration of 5000 cells per well, and cultured in Iscove's medium supplemented with 5 × 10 ¹5 M 2-mercaptoethanol (2-ME), 5% fetal calf serum (FCS; Seralab, Sussex, UK), penicillin 100 U/ml, and streptomycin 100 mg/ml, and serum samples were added. 3 H-thymidine was added after 68 h of culturing, and the cells were harvested 4 h later. The samples were tested in two-fold dilutions and compared with a recombinant mouse IL-6 standard (Genzyme, Cambridge, MA).…”
Section: Il-6 Assaymentioning
confidence: 99%
“…In both cases, the contribution of NK cells to the disease process is dependent on the swift production of interferon-gamma (IFN-g), before antigenspecific responses have come into effect [1,3]. In vitro studies have shown that upon stimulation of human lymphocytes with Staphylococcus aureus antigens, primarily NK cells become activated and produce IFN-g [4,5].…”
Section: Introductionmentioning
confidence: 99%